PKM Pengembangan Bisnis Sulaman Sebagai Industri Kecil Keunggulan Daerah dan Budaya Minang Kabau Di Kanagarian Panampuang Kabupaten Agam Sumatera Barat - Erni Masdupi; Rosyeni Rasyid; Rahmiati Rahmiati (Universitas Negeri Padang, 2018)
The embroidery business is a business that has been hereditary in the village of Ampek Angkek, Agam Regency, West Sumatra Province. But in its development this business still faces several obstacles such as the motives, design, and diversification of embroidery products that are still limited, besides that there has not been a common goal in quality among craftsmen as business owners with their sewing children. Therefore the purpose of this activity is to increase the knowledge and skills of embroidery business partners in developing variations in motifs, designs, and diversification of embroidery products, and can improve the quality and quantity of embroidery products to be highly competitive while remaining grounded in the unique characteristics of Minang. Kabau. This activity was carried out by providing training and mentoring on techniques and how to make various variations of embroidery motifs and designs, as well as developing product diversification. The results of the activity showed an increase in partner knowledge and skills in making various variations of motifs and designs of embroidery products. Furthermore, the product diversification in the form of tablecloths, chair cushions and tissue boxes, with the right embroidery layout and quality as expected.Keywords: Craft embroidery, Product diversification, Quality standards